2023
DOI: 10.1021/jacs.2c10667
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Guided Design of Robust Palladium Catalysts for Selective Aerobic Oxidation of Polyols

Abstract: The palladium complex [(L 1 )Pd(μ-OAc)]2[OTf]2 (L 1 = neocuproine) is a selective catalyst for the aerobic oxidation of vicinal polyols to α-hydroxyketones, but competitive oxidation of the ligand methyl groups limits the turnover number and necessitates high Pd loadings. Replacement of the neocuproine ligand with 2,2′-biquinoline ligands was investigated as a strategy to improve catalyst performance and explore the relationship between ligand structure and reactivity. Evaluation of [(L 2 )Pd(μ-OAc)]2[OTf]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…[10][11][12] Mono-, di-and oligosaccharides have been functionalized with palladium-catalyzed oxidation reactions (Figure 1 A). [13][14][15][16][17][18] In particular, Waymouth's monocationic palladium neocuproine complex 1 (Figure 1B) in combination with terminal oxidants like benzoquinone or oxygen has proven to be a valuable tool, [19][20][21] as it selectively oxidizes the hydroxy group at the C3 position. [17,22,23] The resulting keto group opens routes for further modification of this important class of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Mono-, di-and oligosaccharides have been functionalized with palladium-catalyzed oxidation reactions (Figure 1 A). [13][14][15][16][17][18] In particular, Waymouth's monocationic palladium neocuproine complex 1 (Figure 1B) in combination with terminal oxidants like benzoquinone or oxygen has proven to be a valuable tool, [19][20][21] as it selectively oxidizes the hydroxy group at the C3 position. [17,22,23] The resulting keto group opens routes for further modification of this important class of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because of multiple C–H bonds with similar reactivity in monosaccharide-based molecules, the control of selectivity in C–H modifications to access diverse sugar derivatives is challenging. By employing photoredox catalysis and transition metal catalysis, impressive selective C–H manipulations of carbohydrates, such as epimerization, 4 oxidation, 5 alkylation 6 and alkenylation, 7 have been realized. Recently, the Taylor group developed a site- and stereoselective C–H alkylation of carbohydrates aided by diarylborinic acid and photoredox catalysis (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…This renders C3 the most favored site for oxidation, [19] despite the fact that 1,3diaxial interactions impose steric hindrance on the C3À H. Recent work by the group of Waymouth revealed that the stereo-electronic factors that favor C3À OH oxidation can be overcome with sterically hindered ligands, leading to catalysts that have a reduced C3-selectivity. [20] The selective oxidation of oligomaltosides can be explained by sterics, as the glucose residue at the non-reducing end is the most accessible. [21] The results of these prior studies form an excellent starting point for the development of a model that predicts the siteselectivity of this catalytic oxidation.…”
Section: Introductionmentioning
confidence: 99%